Characterization of Network Inaccessibility in IEEE 802.15.4 Wireless Networks - Rufino, José (2013)
Wireless communications are vulnerable to the presence of errors during the network operation. These errors may be originated from different sources such as external electromagnetic interferences, obstacles in communication path, or even glitches in the communication circuitry. Such origins may lead the medium access control (MAC) layer to deviate from its normal operation (without presence of errors), forcing the execution of additional actions to maintain the network operational. The execution of such actions may imply the occurrence of periods of "communication silence", where the network, although not being failed, is not performing communications. These periods of ``communication silence" are dubbed network inaccessibility, which may induce inaccurate fault detections and deadline misses. Additionally, the occurrence of network inaccessibility may compromise network properties such as predictability, dependability, and timeliness. Thus, this report presents an exhaustive study about network inaccessibility, using the 802.15.4 standard as a case study. All network inaccessibility scenarios are presented, discussing important steps to achieve predictability, dependability, and timeliness in wireless communications.